One ring to bind them – Cohesin's interaction with chromatin fibers. Issue 1 (22nd March 2019) - Moronta-Gines, Macarena; van Staveren, Thomas R.H.; Wendt, Kerstin S.
Abstract : In the nuclei of eukaryotic cells, the genetic information is organized at several levels. First, the DNA is wound around the histone proteins, to form a structure termed as chromatin fiber. This fiber is then arranged into chromatin loops that can cluster together and form higher order structures. This packaging of chromatin provides on one side compaction but also functional compartmentalization. The cohesin complex is a multifunctional ring-shaped multiprotein complex that organizes the chromatin fiber to establish functional domains important for transcriptional regulation, help with DNA damage repair, and ascertain stable inheritance of the genome during cell division. Our current model for cohesin function suggests that cohesin tethers chromatin strands by topologically entrapping them within its ring. To achieve this, cohesin's association with chromatin needs to be very precisely regulated in timing and position on the chromatin strand. Here we will review the current insight in when and where cohesin associates with chromatin and which factors regulate this. Further, we will discuss the latest insights into where and how the cohesin ring opens to embrace chromatin and also the current knowledge about the 'exit gates' when cohesin is released from chromatin.